The Pneumococcal Divisome: Dynamic Control of Streptococcus pneumoniae Cell Division - Briggs, Nicholas S.; Bruce, Kevin E.; Naskar, Souvik; Winkler, Malcolm E.; Roper, David I. (Frontiers in Microbiology, 2021)
Cell division in Streptococcus pneumoniae (pneumococcus) is performed and regulated by a protein complex consisting of at least 14 different protein elements; known as the divisome. Recent findings have advanced our understanding of the molecular events surrounding this process and have provided new understanding of the mechanisms that occur during the division of pneumococcus. This review will provide an overview of the key protein complexes and how they are involved in cell division. We will discuss the interaction of proteins in the divisome complex that underpin the control mechanisms for cell division and cell wall synthesis and remodelling that are required in S. pneumoniae, including the involvement of virulence factors and capsular polysaccharides.